Monitoring global climate change using SLR data from LARES and other geodetic satellites - PAOLOZZI, Antonio; PARIS, Claudio; Pavlis, Erricos C.; SINDONI, GIAMPIERO; CIUFOLINI, IGNAZIO (SPIE Proceedings, Sensors and Smart Structures Technologies for Civil, Mechanical, and Aerospace Systems 2016, 2016)
The Earth Orientation Parameters (EOP), i.e. the spin axis of the Earth, is influenced by the mass redistribution inside and on the surface of the Earth. On the Earth surface, global ice melting, sea level change and atmospheric circulation are the prime contributors. Recent studies have unraveled the majority of the mysteries behind the Chandler wobble, the annual motion and the secular motion of the pole. The differences from the motion of a pole for a rigid Earth is indeed due to the mass redistribution and transfer of angular momentum among the atmosphere, the oceans and solid Earth. The technique of laser ranging and the use of laser ranged satellites such as LARES along with other techniques such Very Long Baseline Interferometry (VLBI) allow to measure the EOP with accuracies at the level of ~200 μas which correspond to few millimeters at the Earth's surface, while the use of Global Navigation Satellite System (GNSS) data can reach an accuracy even below 100 μas. At these unprecedented high levels of accuracy, even tiny anomalous behavior in EOP can be observed and thus correlated to global environmental changes such as ice melting on Greenland and the polar caps, and extreme events that involve strong ocean-atmosphere coupling interactions such as the El Niño. The contribution of Satellite Laser Ranging (SLR) data such as from the LARES mission and similar satellites to this area is outlined in this paper.